Determining Critical Organizational Thresholds: Revealing the Necessary Conditions of Knowledge Sharing, Culture and Leadership for Employee Performance - Iwan Darmawan; Aan Hardiyana; Kadir Kadir (Acman: Accounting and Management Journal, 2026)
This study investigates the structural effects and necessary threshold conditions of Transformational Leadership, Knowledge Sharing, and Organizational Culture on Employee Performance within public sector agencies in Bandung City. By moving beyond traditional linear approaches, the study aims to determine both the direct/indirect causal pathways and the non-compensatory bottleneck conditions required to achieve optimal public sector productivity. The researchers deployed a quantitative survey approach, collecting primary data via 5-point Likert scale questionnaires from 55 public sector employees across government offices in Bandung City. Prior to structural evaluation, measurement scales underwent rigorous validity and reliability testing. The study then utilized a two-stage analytical design: path analysis to test linear direct and indirect hypotheses (Y = 0.386X_1 + 0.357X_2 + 0.287X_3 + epsilon), followed by Necessary Condition Analysis (NCA) to calculate specific bottleneck values and percentage thresholds across low, moderate, and peak performance levels. The path analysis reveals that Transformational Leadership, Knowledge Sharing, and Organizational Culture significantly drive employee performance, collectively accounting for an 89.1% total effect. Furthermore, the NCA findings demonstrate that these three factors operate as non-compensatory prerequisites; failing to meet minimum threshold values in any single construct severely caps performance regardless of how strongly the other dimensions perform. Practically, this study provides public sector managers in Bandung with concrete, actionable bottleneck metrics rather than generic recommendations. Administrators can now prioritize resource allocation according to exact performance targets—ensuring that essential leadership behaviors, knowledge-sharing channels, and cultural norms satisfy baseline necessity thresholds before attempting to maximize secondary organizational drivers. This research offers novel empirical value by integrating conventional path analysis with Necessary Condition Analysis (NCA) within a public administration context. Unlike previous studies that treat leadership, culture, and knowledge sharing as purely additive drivers, this dual-analytical framework identifies both the net predictive effects and the precise necessary bottleneck conditions needed to unlock high-level employee performance.